I/O [compact disc] - Gabriel, Peter, 1950- (Real World Productions, 2023)
More than 20 years in the making, this December finally sees the release of i/o, Peter Gabriel's first album of new material since 2002's Up. During 2023, Peter has been releasing a new song from the album on the occasion of every full moon. Being revealed roughly every four weeks, each track has been allowed to find its own time and space, to enjoy its own orbit. Now it's time to stand back and admire the final, completed creation. And what a creation. Twelve tracks of grace, gravity and great beauty that provide welcome confirmation of not only Peter's ongoing ability to write stop-you-in-your-tracks songs but also of that thrilling voice, still perfectly, delightfully intact. Throughout the album the intelligent and thoughtful, often thought-provoking, songs tackle life and the universe.